Perceptions and human-fauna conflicts in the buffer zone of La Amistad International Park, Costa Rica (UNED Research Journal, 2021)
Introduction: Currently, many animals leave protected wild areas in search of resources, suffering conflicts with people from nearby areas. Objective: To evaluate the conflicts between people and fauna in the Buffer Zone of La Amistad International Park, Costa Rica. Methods: We applied semi-structured interviews and questionnaires in five communities. Results: The most conflictive species in agriculture were Ortalis cinereiceps, Atta cephalotes and Phyllophaga sp.; and in livestock, Panthera onca, Desmodus rotundus and Canis latrans. Losses amount to US$44,000, with Tres Colinas and Santa María de Brunka being the most affected communities, although their inhabitants have both positive and negative opinions of these animals. Conclusion: Six species cause most of the losses in the area, but the inhabitants differ in their perception.
Keywords: communities; deforestation; human-animal interactions; losses; producers